Climate change and opposing spatial conservation priorities for anuran protection in the Brazilian hotspots - Vasconcelos, Tiago S. [UNESP]; Prado, Vitor H. M. (Elsevier B.V., 2019)
In conservation biogeography, the process of spatial conservation prioritization (SCP) aims to select areas that meet biodiversity targets at a minimum set coverage. Here, we propose a SCP scheme for the highly endemic and diverse anuran fauna of the Atlantic Forest (AF) and Cerrado (CER) South American hotspots under different climate change scenarios. Specifically, we make use of predicted anuran occurrences, built for baseline and future (2050 and 2070) time slices, and address biological and conservation metrics to identify potential priority regions for anuran conservation over time using the software MARXAN. Considering each time slice separately, the percentage area needed for total anuran representation varies at magnitudes of 9.8-10.66% for the AF and 6.4-8.8% for the CER. Pooling all time slices together in the selected conservation network, the identified spatial priorities account for 15.56% and 13.25% of the total AF and CER areas respectively. However, we identified opposing strategies for the anuran spatial conservation prioritization in the AF and CER over the different time periods; the increasing of priority cells across time considering the potential species redistribution under climate change in the AF, and the selection of fewer priority cells in the future than the identified for the baseline climate in the CER. The southeastern AF coast was identified as a priority area for amphibian conservation in this hotspot, as well as some other smaller areas in the northern and southern regions. Priority areas identified in the CER, although patchy distributed across the hotspot, are found in specific central-northern, western, and southeastern regions. The different conservation strategies identified in the present SCP emphasize the need for establishing different conservation efforts according to a sequential scheduling of priority areas that optimizes the long-term conservation goals.
Keywords: Atlantic Forest; Cerrado; Ecological niche modelling; MARXAN software; Spatial conservation prioritization